Centre for Tropical Veterinary Medicine, Scotland - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The production of animals in the tropics is becoming progressively more difficult as more land is needed for alternative uses. Countries struggling with economic difficulties cannot always provide the physical inputs required for livestock...